Education legislation,1967. Hearings before the subcommittee on education of the committee on labor and public welfare United States Senate 19th congress, 1st session on S.1125 and H.R.7819... - U.S.Government Printing Office (U.S.Government, 1967)
vi, 1597-1863 p.; 23 cm.